Local Wisdom in Lengsir Wengi Song - Ali Alamsyah Kusumadinata; Septian Juliansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The song of Lengsir Wengi is a composed song from Sunan Kalijaga and is a song that contains local values and zikir values. This belief became a ritual on certain days of the Javanese calendar. The purpose of this study is to find other meanings from the perspective of local wisdom in the work of Lengsir Wengi songs. The research method is classified as qualitative research with an interpretive approach using Barthes semiotics. The results showed that spiritual songs are a way of proselytizing from Sunan Kalijaga to the Javanese people who never forget their culture. The ability of this song gave birth to enculturation communication, later generations brought this song as part of a spell (means: jampi) and treatment for sick children and so on. The development of songs or (means: tembang) has its own position as part of folklore which leads to the value of trust and hope in facing life's increasingly difficult challenges and often undergoing changes.